DDQ in mechanochemical C–N coupling reactions - Bera, Shyamal Kanti; Bhanja, Rosalin; Mal, Prasenjit (Beilstein Journal of Organic Chemistry, 2022)
2,3-Dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) is a commonly known oxidant. Herein, we report that DDQ can be used to synthesize 1,2-disubstituted benzimidazoles and quinazolin-4(3H)-ones via the intra- and intermolecular C–N coupling reaction under solvent-free mechanochemical (ball milling) conditions. In the presence of DDQ, the intramolecular C(sp2)–H amidation of N-(2-(arylideneamino)phenyl)-p-toluenesulfonamides leads to 1,2-disubstituted benzimidazoles and the one-pot coupling of 2-aminobenzamides with aryl/alkyl aldehydes resulted in substituted quinazolin-4(3H)-one derivatives in high yields.
Keywords: ball mill; 1H-benzo[d]imidazole; C(sp2)–H amidation; DDQ; mechanochemistry; quinazolin-4(3H)-one